INTEGRATING DIGITAL DOCUMENTATION AND COMMUNITY ENGAGEMENT: ‘UNVEILING THE HIDDEN HAMINA’ INTERNATIONAL SUMMER SCHOOL - J. Garcia-Fernandez; L. Medeiros (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
Currently, non-formal Heritage Education strategies present an immense potential to valorise and protect cultural heritage (CH), while promoting the transmission and production of knowledge. Integrating the potential of technologies in cultural heritage management practices, particularly in the field of ‘heritage documentation’, presents a way to empower both experts and non-experts with tools to better understand and record CH assets. It also allows to use research to advance on conservation, and to create and strengthen links between communities and their heritage. To achieve these in a non-formal context, a learning process/path needs to go beyond merely taking the contents out of the classroom; it requires the development of a strategy where students interact directly of the heritage assets, the communities and the institutions during a continuous amount of time, allowing for immersion, meaningful experience, and dialogue. In 2018, under coordination of the University of Lisbon and Tampere University of Technology, took place the International Summer School ‘Unveiling the Hidden Hamina’, in Finland. The course was focused on integrating a non-formal academic course on Heritage documentation with a community-centred approach to cultural heritage. Its primary goals were to develop a learning path merging communities and course contents, to tackle current challenges in Heritage documentation, and to solve some current problems identified by local CH institutions. This paper provides a description of the course program and learning activities, the community engagement strategies, the integrated socio-cultural agenda and the main outcomes obtained by the course.